Pengaruh Komitmen kerja, Motivasi Kerja dan Loyalitas Pegawai terhadap Keterlibatan Kerja Pegawai Kantor Dinas Pertanian Kota Denpasar - Rahayuningtyas, Lucky Sintya; Fauzan, Mohammad (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The objectives of the study are (1) Analyze and explain the effect of work commitment on employee work engagement; (2) Analyze and explain the effect of work motivation on employee work engagement; (3) Analyze and explain the effect of work loyalty on the work involvement of employees of the Denpasar City Agricultural Office. This research is a type of explanatory research, which is testing hypotheses and explaining the influence between variables of hypotheses that have been formulated. The research sample was 100 employees at the Denpasar City Agriculture Office using the porposive sampling method. The research data was obtained through the distribution of questionnaires through a googleform link to employees of the Denpasar City Agricultural Office, then the data was processed using SPSS version 26. For the purposes of data analysis, instrument tests are carried out by conducting validity tests and Reliability test; Test the model through Test F, and Test determination (R²) and then Test Hypothesis (Test t). The findings of the study are (1) Work Commitment has a positive effect on Work Engagement; (2) Intrinsic Motivation positively affects Work engagement; (3) Employee Loyalty does not affect the Work Involvement of Denpasar City Agricultural Office Employees. Based on the research findings that work involvement is influenced by employee work commitment and intrinsic motivation, employee recruitment must consider the assessment of work commitment and intrinsic motivation of prospective employees.